DEVELOPMENT OF A LIGHTWEIGHT INTERACTIVE ONLINE TESTING SYSTEM USING FRONT-END WEB TECHNOLOGIES - Gavharoy Xoshimova Sohibjon qizi (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract: This research presents the design and implementation of a lightweight online testing system aimed at improving student assessment through web technologies. The system is developed using HTML, CSS, and JavaScript, focusing on simplicity, accessibility, and real-time interaction without relying on complex server-side components. The proposed platform enables users to complete tests in a digital environment and instantly receive evaluation results. The structural components are organized with HTML, while CSS ensures a responsive and user-friendly interface. JavaScript is responsible for handling dynamic processes such as user input processing, answer verification, and automatic score calculation. The findings indicate that the developed system enhances user engagement and significantly reduces the time required for assessment. In addition, the platform can be easily adapted for different educational contexts. Future improvements may include integration with databases, user authentication mechanisms, and advanced performance analytics.